Radovan Jaut iz Voličine in njegove vloge med nemško okupacijo - Toš, Marjan (Časopis za zgodovino in narodopisje, 2025)
The area of central Slovenske gorice (today’s municipalities of Benedikt, Cerkvenjak, Lenart, Sveta Trojica, Sveti Jurij v Slovenskih goricah, and Sveta Ana) belonged to that part of occupied Slovenia which was seized by Germany in 1941. As elsewhere in Slovenian Styria, a thoroughly developed German occupation system was also in force in Slovenske gorice. For Slovenian Styria the Nazis envisaged annexation and denationalization in the most complete manner and in the shortest possible time, and they also began to implement this most consistently. Administratively, during the German occupation of Slovenian Styria 1941–1945, central Slovenske gorice first belonged to the Ptuj district and then until the end of the occupation to the Ptuj county. Altogether in June 1941 there were 41 municipalities in the Ptuj county.2 The central role in the process of Germanizing the Slovenian population in Lower Styria was entrusted by the occupying authorities to the Styrian Homeland Union (Der Steirische Heimatbund). T he German occupation authorities renamed Voličina, which is still part of the municipality of Lenart, as the municipality of Strahleck (Gemeinde Strahleck). They also Germanized all the other settlements in this area and enforced their denationalization policy with offensive Germanization in all areas, especially in the school and in the German kindergarten. This paper outlines the role of the German school during the occupation and of its head teacher Radovan Jaut, whose fate after the war remains unresolved and unknown.
Keywords: germanizacija; Germanization; Jaut; Niko; occupation; odpor; okupacija; oresistance; Tanja